Influence of chronic alcoholism and oestrogen deficiency on the variation of stoichiometry of hydroxyapatite within alveolar bone crest of rats - Marchini, Adriana M. P. S. [UNESP]; Deco, Camila P. [UNESP]; Lodi, Karina B. [UNESP]; Marchini, Leonardo [UNESP]; Santo, Ana M. E.; Rocha, Rosilene F. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Objective: Previous findings suggest that chronic alcoholism and oestrogenic deficiency may affect bones in general (including alveolar bone) and increase individuals' susceptibility to the development of periodontal disease. The aim of this study was to assess possible alterations in the chemical composition of alveolar bone in rats subjected to chronic alcoholism, oestrogen deficiency or both.Design: Fifty-four rats were initially divided into two groups: ovariectomized (Ovx), and Sham operated (Sham). A month after surgery, the groups were sub-divided and received the following dietary intervention for eight weeks: 20% alcohol, isocaloric diet and ad libitum diet. Samples of the mandible, in the alveolar bone crest region, were analyzed to verify possible changes in the stoichiometric composition of bone hydroxyapatite, by measuring the relationship between the concentration of calcium and phosphorus (Ca/P ratios), using micro X-ray fluorescence spectrometry.Results: The ad libitum groups presented the highest average values of Ca/P ratios, while the groups with dietary restrictions presented the smallest average values. The Ovx ad libitum group presented the highest values of Ca/P ratios (2.03 +/- 0.04). However, these values were not considered statistically different (p > 0.05) from the Sham ad libitum group (2.01 +/- 0.01). The Ovx alcohol group presented lower values for Ca/P ratios (1.92 +/- 0.06), being the only group statistically different (p < 0.001) from the Sham ad libitum group. Potential confounding variables are discussed.Conclusion: Ovariectomy associated with alcohol consumption at 20% significantly changed the stoichiometry composition of hydroxyapatite in the alveolar bone crest, leading to a reduction in Ca/P ratios. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Alcoholism; Ovariectomy; Periodontium; Fluorescence spectrometry; Calcium; Phosphorous